Relevansi Pemikiran Syekh Muhammad Arsyad al-Banjari dalam Membangun Generasi Emas 2045 - Syukri, M.; Hermansyah (Borneo : Journal of Islamic Studies, 2025)
This study aims to review the thoughts of Sheikh Muhammad Arsyad al-Banjari and examine their relevance in forming the foundation of the future generation of Indonesia. The thinking of the scholars of Borneo and the archipelago is very important to be studied in order to contribute to the development of quality human resources towards a golden Indonesia 2045. The method used in this study through a qualitative approach with literature review, this article highlights aspects of education, law, and spirituality contained in his legacy with primary sources of the book Sabilal Muhtadin and secondary sources of articles, books, and other sources that can support the data from this study. The results of the study indicate that the thoughts of Sheikh Muhammad Arsyad al Banjari in building the golden generation of 2045 are implied in his works which are very famous among Muslims in Borneo and even the archipelago, including quality and equitable education, health and nutrition of the younger generation, and economic independence and entrepreneurship. Sheikh Muhammad Arsyad al Banjari's thoughts, when compared with the pillars of the vision of a golden Indonesia 2045, are included in the pillars of human development and mastery of science and technology, sustainable economic development, and governance.